A prospective observational analytical study on Rouviere’s sulcus: a single institutional study - Mishra, Bana Bihari; Acharya, Archana Kumari; Dash, Jyoti Ranjan; Sahu, Debabrata (International Surgery Journal, 2020)
Background: Laparoscopic cholecystectomy is the most commonly performed laparoscopic surgery worldwide. Safe cholecystectomy is the priority to reduce the morbidity and mortality. There is a paradigm shift from extensive Calot’s dissection to identification of Rouviere’s sulcus and lesser dissection. Identification and analysis of Rouviere’s sulcus will help us doing a safe cholecystectomy and avoiding further injuries to bile ducts. Methods: The study included 160 cases of laparoscopic cholecystectomy, posted in elective OT and identified Rouviere’s sulcus during laparoscopy. Table visual inspection and analysis was done. And the collected data was analyzed for different types of sulcus, its position, morphology and content. Results: Of 160 cases, 147 cases had Rouviere’s sulcus. 13 cases did not have a sulcus. Open type sulcus was present in 99 cases, 35 had closed type, whereas 19 had slit type and only 7 had a scar like sulcus. The study showed 92% of our patients had Rouviere’s sulcus and of them 61.9% had an open type which was the most common type of sulcus of them 18 cases had a visible pulsating vessel in the floor of the sulcus i.e. posterior sectional pedicle in the sulcus. Conclusions: Present study showed, in 92% cases it is easy and approachable to visualise the Rouvier’s sulcus. So, it is feasible and beneficial to identify the sulcus and keep the dissection above this level to avoid common bile duct injury and further complication thereof.